Ab-initio calculatio of the physical properties of XFeB4 (X=Y and Sc) - Benlahbib, Maria; Gueddouh, Ahmed (Université Amar Telidji - Laghouat - Département des sciences de la matière, 2020)
The aim of this thesis is the ab initio calculation of the properties: structural, electronic, hardness and clastic anisotropy of two compounds: XFeB4 (X- Y, Sc). The calculation is conducted in the framework of the functional theory of density (DFT) through the pseudo potential method (PP) with the peneralized gradient approximation of Perdew-Burke Emzerhof (GGA-PBE), which is implanted in the CASTEP code. The results are discussed and compared with experimental data. A good agreement is find between the results in the fundamental state and those from the experimental. For a comprehensive description of the mechanical behavior of the considered, I first calculate their elastic constants of single crystal state, ie the anisotropic elastic constants Cij. We have plotted the three dimensional (3D) surfaces and planar contours of bulk and Young moduli of XFeB4 (X- Y, Sc). structures at several crystallographic planes, ((100), (010) and (001)) to reveal thecir elastic anisotropy.